Pornography and sexual satisfaction - Any relationship? - Štulhofer, Aleksandar; Landripet, Ivan; Momčilović, Aco; Matko, Vlasta; Kladarić, Predrag; Buško, Vesna (2007)
A huge increase in the supply of and exposure to pornography has not been met by intensified research efforts to analyze potential effects of pornography on young people’s sexual socialization. Whether what we need is a “reconceptualization of harm from exposure to erotica” or a more broad and sex-positive emphasis on the myriad of ways pornography can affect young people’s sexual health, the importance of new research on (cyber)pornography seems undisputed. Our ambition was to find out whether pornography plays a role in shaping sexual identities and expectations, and whether it contributes to the construction of young women and men’s “internalized working models” of their and others’ sexuality. We surveyed on-line young women and men (N=1.914) asking them about their experiences with pornography from the age of 14 on, sexual preferences, relationships and intimacy. In order to conceptualize indirect effects of pornography, we relied on the sexual script theory of sexual socialization. Our model stipulates the role of pornography in the process of intrapersonal sexual script construction, which is mediated by individual evaluation of pornographic materials. The evaluation is dependent on several intrapersonal (personality traits), interpersonal (social isolation, prior sexual experience) and socio-cultural (gender-specific norms and expectations) factors. The interplay of all these (sequentially structured) factors was expected to determine the actual level of sexual satisfaction. To enable measurement of the impact of pornography on sexual scripting, the authors developed an original tool, the Sexual Script Overlap Scale (SSOS), which provides a quantifiable insight into the process of pornographic “colonization” of sexual scripts. In the case of women, structural modeling suggested that the effect of pornography on young women’s sexual satisfaction was mediated primarily by the negative impact of scripting on intimacy. Pornography consumption was positively related to overlap between the porn script and the “good sex” script, which in turn was negatively associated with the level of intimacy with one’s partner. In contrast, both positive and negative indirect effects of pornography on young men’s sexual satisfaction were observed. While the negative impact was mediated by the scripting process and intimacy (more pornography consumption, less intimacy), the positive impact was mediated by scripting and sexual experience. As in the case of women, the association between pornography consumption and sexual experience was both direct and indirect.
Projekt MZOS
ENG